Normative legal regulation of private detective services in Slovenia – research-based proposals for legislative changes. (14th June 2022) - Sotlar, Andrej; Modic, Maja; Dvojmoč, Miha
The findings of the research on private detective services in the Republic of Slovenia suggest that taking into account the principle of respect for human rights and freedoms, and at the same time efficient provision of private detective services, it is necessary to adopt some normative legal changes in the field of private detective services. These changes are the following: a proper definition of private detective services in the standard classification of activities; a change in the scope of work of private detectives; more appropriate definition of personal detection and supplementing entitlements in terms of adding new and expanding existing ones; regulation of the field of 'internal supervisors', 'contractual supervisors', and 'lay controllers' in relation to private detective services, where there are several options of regulation, but where the protection of public interest and ensuring the protection of human rights and freedoms are crucial.